Porous materials from sponge titanium powders with increased strength - V. V. Savich; M. V. Tumilovich; L. P. Pilinevich; A. M. Taraykovich (Литьë и металлургия)
The possibility of increasing the mechanical strength of porous materials from sponge titanium powders by two methods has been investigated. In the first case, sintering activation was carried out using alloying additives based on Al, ZnO and TiH2. It was found that the maximum (1.8–1.9 times) increase in strength compared to samples made only from titanium powder is achieved by adding up to 0.5 % TiH2. With the introduction of other alloying additives (Al, ZnO), the mechanical strength increases by no more than 16–20 %. The influence of sintering regimes and atmosphere on the mechanical strength of porous titanium has been studied. It is shown that samples sintered in a vacuum have 1.85–1.90 times higher mechanical strength compared to the same samples sintered in an argon atmosphere. In the second case, to increase the mechanical strength of porous titanium, it was proposed to use bidisperse mixtures consisting of fine and coarse titanium powders. For this purpose, up to 20 wt.% of a fine titanium powder with a particle size of 100–160, 40–100 or <40 μm was added to the titanium sponge powder with a particle size of 630–1000 μm. It was found that the introduction of 10–12 wt.% of the finest (<40 μm) titanium powder leads to a 4‑fold increase in the tensile strength of the porous material compared to porous materials made only from coarse (630–1000 μm) titanium powder of the same chemical composition.